Circulation of Enterovirus D68 during Period of Increased Influenza-Like Illness, Maryland, USA, 2021 - Fall, Amary; Gallagher, Nicholas; Morris, C. Paul; Norton, Julie M.; Pekosz, Andrew; Klein, Eili; Mostafa, Heba H. (Emerging infectious diseases, 2022)
We report enterovirus D68 circulation in Maryland, USA, during September-October 2021, which was associated with a spike in influenza-like illness. The characterized enterovirus D68 genomes clustered within the B3 subclade that circulated in 2018 in Europe and the United States.